THE DIETARY PATTERNS AND THE RISK OF BREAST CANCER - L. A. Radkevich; D. A. Radkevich (Исследования и практика в медицине, 2016)
Malnutrition in the early stages of life cause hypomotilinemia and shape the epigenome, and does not change the genetic code. Increasing the frequency of non-communicable chronic diseases (NCDS) in the world associated with influence of external factors, including poor diet and obesity .Purpose. A comparative study of dietary patterns in countries with similar social conditions but with different frequency of breast cancer.Materials and methods. Data on incidence of breast cancer in 160 countries is selected from the database GLOBOCAN 2008. Levels of consumption of food and nutrients (53 species) for each country selected from the FAO database for 1990–2005 and 2003–2005 years. The power structure of countries were represented in the form of a total daily level of consumption (DLC) (g/person/day), and also in the form of blocks of products with common source of origin (g/person/day): animal products, grains, vegetables”, “fruit drinks”, “alcoholic beverages”; “nutrients of animal products” (%): energy, protein, fat; “full of nutrients” (%): carbohydrates, proteins, fats; energy (kcal/person/day), proteins and fats (g/person/day). Determined the percent contribution of each block in the structure of food in the total daily consumption of food and nutrients (DLC). In the comparative analysis used as a predictor of the metabolic syndrome: body mass index (BMI ≥ 25 kg/m2) and blood cholesterol (NF ≥ 50 mmol/l).Results. Under similar social and geographical conditions in countries with a high incidence of breast cancer part of the power Structure were represented: 36% of “animal products”, 37% “of grain and vegetables,” 14% “fruits and beverages”, 13% “alcoholic beverages”. In the Mediterranean countries with a low incidence of breast cancer: 28% of “animal products”, 55% “grain & vegetables 11% fruits & drink”, 5% “alcoholic beverages”. In countries with a high incidence of breast cancer Nutrients “animal products” in 1,5 times more than in the Mediterranean countries with a low incidence of breast cancer.Conclusions. The food pattern has modifying effects on the risk of breast cancer.